6(n+2)=(6+3n)

Simple and best practice solution for 6(n+2)=(6+3n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(n+2)=(6+3n) equation:


Simplifying
6(n + 2) = (6 + 3n)

Reorder the terms:
6(2 + n) = (6 + 3n)
(2 * 6 + n * 6) = (6 + 3n)
(12 + 6n) = (6 + 3n)

Remove parenthesis around (6 + 3n)
12 + 6n = 6 + 3n

Solving
12 + 6n = 6 + 3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3n' to each side of the equation.
12 + 6n + -3n = 6 + 3n + -3n

Combine like terms: 6n + -3n = 3n
12 + 3n = 6 + 3n + -3n

Combine like terms: 3n + -3n = 0
12 + 3n = 6 + 0
12 + 3n = 6

Add '-12' to each side of the equation.
12 + -12 + 3n = 6 + -12

Combine like terms: 12 + -12 = 0
0 + 3n = 6 + -12
3n = 6 + -12

Combine like terms: 6 + -12 = -6
3n = -6

Divide each side by '3'.
n = -2

Simplifying
n = -2

See similar equations:

| 8x+8=7x-7 | | (X-2.3)(2x+5.1)=24.3 | | -30x=-4 | | 400=25n | | 5-(9/2)x=32 | | w=4/xyz | | -(.79m+.227)=-(2.09m+.838) | | 10(n+8)=2(40+5) | | Rs=2x+10 | | 1x^2-9x-2=0 | | 192t^2-243=0 | | 6(0)-18=42x | | 10(x-40/5) | | 4x^2-6x+8=6x-3+3x^2 | | 6-3(4x+1)=2x-3(3x+9) | | 2/7(4x-18) | | 5(x+3)-5=18-6x-8+11x | | 6c^3+9c^2= | | -3z+z=-3z-7-6z | | (8z^4-4z^3+4)2z^5= | | 6+8(8k+2)=-298 | | -7y=14/9 | | (15-4x)+(2x-6)=0 | | X/243=4/27 | | -6/5w=-36 | | 2x^2-4x=-4x+x^2+25 | | X/108=8/9 | | 4y-7=8+1y | | solvea=s(1-dn)forn | | -7y/6=-35 | | (4x)+(2x-7)=7x-10 | | n^2-4n+24=0 |

Equations solver categories